PENYIDIKAN KECELAKAAN LALU LINTAS MELALUI PENDEKATAN RESTORATIVE JUSTICE DI KEPOLISIAN RESORT TABANAN - Nurianto Rachmad Soepadmo (Universitas Mahendradatta, 2022)
This study aims to determine the investigation of traffic accidents through a restorative justice approach. This research is a normative legal research with a statutory approach and a case approach. This research took place at the Resort Police of Tabanan Regency, Bali with the object of research being the case of a traffic accident. Every case in every traffic accident must be resolved in accordance with the provisions of the legislation. The settlement of traffic accidents that have been carried out through a restorative justice approach in the jurisdiction of the Tabanan Resort Police can be done by 1) Alternative Dispute Resolution, namely alternative dispute resolution, dispute resolution options outside the court, and cooperative dispute resolution mechanisms. 2) Diversion Settlement which is the transfer of the settlement of children's cases from the criminal justice process to a process outside the criminal justice system, as referred to in Article 1 number 7 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The obstacles in investigating traffic accidents with a restorative justice approach in the Tabanan Resort jurisdiction are the competence of investigators at the Tabanan Police Criminal Investigation Unit in the field of legal knowledge, statutory regulations, the criminal justice system and technical and tactical investigation skills are still not optimal.